RESEARCH PROFESSIONAL TRAINING OF SPECIALISTS ECONOMIC SECTOR IN HIGHER EDUCATION INSTITUTIONS OF THE REPUBLIC OF POLAND AND UKRAINE: CONCEPTUAL BASES - Zagorodnya., A. (Continuing Professional Education: Theory and Practice, 2023)
The author reveals the concept of research of professional training in the field of economic higher education institutions of the Republic of Poland and Ukraine. The author argues that the concept of professional training of future economists in universities reflects provisions for their training competency based approach to the content, methods, means and forms of education and individual approach, which ensures the comprehensive development of future professionals economic sector. Study of the subject - professional training economic sector in higher education institutions of the Republic of Poland and Ukraine - was based on scientifically based position that economic education in Poland and Ukraine as an important socioeconomic resource reproduction of human capital, efficient socio-educational, spiritual, political, multicultural development. Under such conditions the research training of future specialists in economics aimed at identifying similarities and differences in national economic development education in selected countries. Methodological condition survey is provision for consideration of the importance of historical, political, economic, educational and cultural characteristics of each country, their influence on the development of education in general and the economic aspect of it in particular. The leading idea conceptual study of the subject is a priority monographic (individual) study of economic education in Poland and Ukraine, which allows comparative analysis of vocational training of the future professionals of the economic sector in higher educational institutions of Poland and Ukraine